Conversational analysis in aphasia - Gayathri H (Journal of All India Institute of Speech and Hearing, 1970)
The smooth flow of thoughts and ideas that is characteristic of communication between normal individuals may be absent in case of aphasics and a communicationgap may exist between an aphasic person and his interlocutor. Despite this fact it is also known that the aphasic person retains the functional use of language tosome extent